Cek-Prodaku: Standarisasi Mutu Produk Halal Umkm untuk Memenuhi Pasar Global - Ike Dwi Astuti; Andi Moh. Abrianto; Ikhsan Naufal Dwilaksana (Jurnal Ilmiah Ekonomi Islam, 2022)
Entering the Industry 4.0 era, the market share opportunity is very high, the market need for quality products is the main standard. The problems faced by MSME actors are the lack of specific quality assurance for MSME products, the lack of efficiency in the process of producing goods, and the lack of assistance to improve product quality, causing the growth of MSME products to become unstable. CEK-PRODAKU as an application designed as a service to standardize product quality from producers to product certification bodies and provide assistance more efficiently and effectively by using a mutual of connection system. So that it is possible for this application to improve the quality of product quality in accordance with SNI certified standards as well as assistance for SMEs to improve the quality of domestic products. This study uses research and development methods, namely designing the needs of MSMEs with user friendly-based applications, this research was carried out to the stage of needs analysis and application design.